The groove hypothesis—music and dance reimagined: A sensory motor synchronization study - Hiro Fumi Akao (PLoS ONE, 2025)
Perfect synchronization, although essential in ensembles, has not been objectively evaluated. Further, the closely associated backbeat feel has not been adequately explained in the literature. This study introduces the groove hypothesis as a novel strategy for achieving perfect synchronization in musical ensembles, particularly in tasks involving backbeat feel. In ensemble playing, musicians must begin their movements before hearing the sounds of others to achieve synchronization. Conversely, in professional music settings, it is believed that target times are shared with an error of ±5ms based on experience, and this is considered perfect synchronization. Furthermore, while the word “groove” is used in various ways, here, it introduces the perspective of those who play groove. By examining the performance of participants using electronic drums with a 65-ms response delay, I identified two distinct synchronization strategies, shedding new light on how musicians and dancers manage rhythmic coordination. Based on the experimental results, the participants (ten university students and four dancers) were divided into Group A, which included six participants who could synchronize, and Group B, which included eight participants whose synchronization was delayed. Their p-values indicated that Group A used different strategies for the two plays. While the metrical swing theory explains why we can match a rhythm, I propose the groove hypothesis as a synchronization strategy for musicians: achieving perfect synchronization facilitated by imagining walking or running. The hypothesis suggests that we are aware of the motion of the center of gravity and that this awareness can be linguistically represented as a quiet inner “singing” in the brain. This idea is a new approach to music and dance performances and is also a proposal for cognitive science that suggests the possibility of linguistic imagery being involved in the perception of musical rhythms and synchronized movement of the body.